Balance Circumstances of Planetary Atmospheres and Causes of Gaseous Escape and Collapse of Earth's Ozone Layer - Ohan, Armen (Geography, Earth Science and Environment: Research Highlights Vol. 9, 2025)
Understanding the mechanism of the planetary atmosphere and the forces involved in balance circumstances may help to know how gaseous escape occurs and guide the ways to reduce its rate via preserving the most important factors of Earth’s ecosystem, where the balance circumstances of the planetary atmosphere can be defined as the balance among a group of dynamic and static forces that determines the volume and pressure of gases of the planetary atmosphere. The first force is the gravitational force of the planet that attracts gases from space to confine them within the range of the planet's gravitational field, and the value of this force varies among the planets of the solar system due to the differences in their masses. The second main force is the thermodynamic effects that generated as a result of the gaseous expansion that depends on the value of their temperature due to the increase in the kinetic energy resulted of the atomic and molecule collision of the gaseous elements of the atmosphere and their values change according to the value of the planet's temperature that results from their differences in their distances from the Sun, all planetary atmospheres have a specific state of equilibrium within the different circumferences, physic characteristics of elements and amount of gases in the atmosphere, the total result of these forces is determines the specific feature of the balance circumstances of each planetary atmosphere according to the value of the planet's gravitational force and the value of generated dynamic forces due to the expansion of gases according to the temperature of the planet as well as the physical characteristics of atmospheric elements such (boiling, liquefaction and solidification temperature) that differs according to the physical properties of elements that are strongly affected by their mass weight.